The Juridical Analysis of the Implementation of the Notary's Recusal Rights in Maintaining the Confidentiality of the Contents of the Deed - Yudana, Median Eka; Sulchan, Achmad (Jurnal Konstatering, 2024)
This research aims to analyze: 1) The application of the notary's right of recusal in maintaining the confidentiality of the contents of the deed he or she has made as regulated in the UUJN is not absolute, considering that it is still possible if other laws order it. Thus, the Notary cannot use his Right of Rejection if the deed he makes is related to Corruption Crimes (Law Number 31 of 1999 which has been amended by Law Number 20 of 2001 concerning the Eradication of Corruption Crimes) and Tax Violations (Law Number 14 of 2002 concerning the Tax Court ). The use of the Right of Refusal when a Notary is a witness in a court trial is not immediate, meaning it takes effect immediately. But if the notary wants to use his right of refusal, he is obliged to come and fulfill the summons and must make a letter of request to the judge who is hearing/examining the case, that the notary will use his right of refusal. Upon the Notary's request, the Judge examining the case in question will determine whether to grant or reject the Notary's request. 2) The legal consequences for a notary who discloses the confidentiality of the contents of the deed he or she has made may result in sanctions, namely criminal threats, civil threats and sanctions according to the Law on Notary Positions ranging from a reprimand to dishonorable dismissal. However, notaries will be given legal protection for Notaries who reveal the contents of the deed, namely Notaries who reveal the contents of the deed with the approval of the interested parties to maintain public trust in the Notary profession and/or Notaries who, because of their position, are asked to explain the contents of the Deed they have made before the court, automatically the Notary receive legal protection as a witness and are free from all charges.